Early Childhood Education Teachers: Perceptions about Their Preservice Training - Rosa Eva Valle-Flórez; María Jesús Colmenero-Ruiz; Pedro Jurado-; Sheila García-Martín (MDPI AG, 2024)
Teacher professional development (TPD) is a process that ensures that teachers acquire the skills necessary to address the complex needs of 21st century children. To this end, over the last decade, the European Higher Education Area (EHEA) has undergone modifications, incorporating active and innovative methodologies in the study plans. Aligned with these principles, this research aims to evaluate the reforms implemented in Spanish universities for the initial training of early childhood education teachers. The opinions of 1048 future teachers from four Spanish universities were collected through a Likert-type questionnaire, measuring students' perceptions of four factors: curricular design/planning, curricular implementation, evaluation strategies, and participation and interaction in the classroom. Perceptions on the first two factors are considered adequate and satisfactory, while problems persist in the third and fourth factors. Considering the results, we reflect on areas for improvement to provide early childhood education professionals with competencies in line with future roles and demands.